2022
DOI: 10.1039/d1fo03206b
|View full text |Cite
|
Sign up to set email alerts
|

The potential of probiotics in the amelioration of hyperuricemia

Abstract: Hyperuricemia is a common disease caused by metabolic disorders or excessive intake of high-purine foods. Persistent hyperuricemia in extreme cases induces gout, and asymptomatic hyperuricemia is probably linked to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 190 publications
1
27
0
Order By: Relevance
“…Particularly, L. paracasei X11 treatment increased the abundance of some beneficial gut microbes, such as Faecalibaculum , which was reported to produce SCFAs to ameliorate tumor progression ( 28 ). More importantly, it was reported that there was a strong correlation between the gut microbiota and inflammatory cytokines of the immune-inflammatory pathways ( 35 ), which was consistent with the phenomena observed in our study. These results could be inferred that L. paracasei X11 might regulate intestinal immune homeostasis via the gut microbiota in HUA mice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Particularly, L. paracasei X11 treatment increased the abundance of some beneficial gut microbes, such as Faecalibaculum , which was reported to produce SCFAs to ameliorate tumor progression ( 28 ). More importantly, it was reported that there was a strong correlation between the gut microbiota and inflammatory cytokines of the immune-inflammatory pathways ( 35 ), which was consistent with the phenomena observed in our study. These results could be inferred that L. paracasei X11 might regulate intestinal immune homeostasis via the gut microbiota in HUA mice.…”
Section: Discussionsupporting
confidence: 93%
“…The diversity and the abundance of gut microbiota in the MOD group were largely lessened compared to those of the CON group, which were moderated and improved by L. paracasei X11 administration. Furthermore, the α-diversity and β-diversity of microbiota could be used to predict the activation of cells and dynamic balance of gut flora ( 35 ), which became a normal microbial community in the X11 group. At the phylum level, L. paracasei X11 alleviated the relative abundance of Bacteroidetes and Proteobacteria and adjusted the proportion of Bacteroidetes to Firmicutes to the normal level.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have found that gut microbiota imbalances exist in patients with HUA and gout ( Chu et al., 2021 ; Yin et al., 2022 ). In addition, the gut microbiota can be altered after UA reduction ( Yu et al., 2018 ), and probiotics may have UA-lowering effects ( Wu et al., 2021 ; Zhao and Lu, 2022 ). Therefore, an in-depth study of the relationship between gut microbes and HUA and gout is expected to make it a target for the prevention and treatment of related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperuricemia can cause gout and other metabolic disorders, it often occurs as a result of metabolic problems or an excessive intake of purine-rich foods ( Zhao et al., 2022 ). Probiotics have been demonstrated the potential to ameliorate hyperuricemia in animals.…”
Section: Discussionmentioning
confidence: 99%